2013
DOI: 10.4414/cvm.2012.00115
|View full text |Cite
|
Sign up to set email alerts
|

Early versus late initial echocardiographic assessment in infective endocarditis: similar findings and no difference in clinical outcome

Abstract: SummaryBackground: The optimal timing of the initial echocardiographic assessment and the influence of microorganisms on echocardiographic findings in patients with infective endocarditis (IE) are not well studied.Methods: In 274 patients with IE, we studied the impact of antibiotic treatment duration of ≤2 days (early, 119 patients) or >2 days (late, 144 patients) prior to diagnostic echocardiography on IE specific findings and on clinical outcomes. Results were stratified for patients with Staphylococcus aur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
4
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 33 publications
5
4
1
Order By: Relevance
“…In our study, men were more likely to have aortic valve IE, which is partly adherent to previous studies [27,28]. The rates of in-hospital mortality and surgical treatment for IE in our study did not differ between men and women, which does not accord with previous reports indicating that women have higher mortality and receive surgical treatment to a lesser extent compared with men [10]. In our cohort, the in-hospital mortality rate was low (7%), which contrasts with previously reported rates of 15-20% [29,30], but is more in line with a Swedish study presenting a 30-days crude mortality rate of 10.4% [3].…”
Section: Gender Differencessupporting
confidence: 87%
See 4 more Smart Citations
“…In our study, men were more likely to have aortic valve IE, which is partly adherent to previous studies [27,28]. The rates of in-hospital mortality and surgical treatment for IE in our study did not differ between men and women, which does not accord with previous reports indicating that women have higher mortality and receive surgical treatment to a lesser extent compared with men [10]. In our cohort, the in-hospital mortality rate was low (7%), which contrasts with previously reported rates of 15-20% [29,30], but is more in line with a Swedish study presenting a 30-days crude mortality rate of 10.4% [3].…”
Section: Gender Differencessupporting
confidence: 87%
“…Furthermore, we found that S. aureus infections were associated with tricuspid valve IE, which is supported by Bonetti et al in their study of 274 patients with IE [10].…”
Section: Differences Over Timesupporting
confidence: 86%
See 3 more Smart Citations